Continuous production of food grade dextran by immobilized cells of weissellaconfusa - B. SRINIVAS; P. NAGA PADMA (International Journal of Pharma and Bio Sciences, 2016)
Dextran a bacterial exopolysaccharide and a long chain polymer of glucose is produced by different microorganisms like Leuconostoc mesenteroides, Lactobacillus spp, Weissella spp and Streptococcus mutans. It has a wide range of application in the food, pharmaceutical and other industries and so is emerging as new and industrially significant product. In the present study the cells of Weissella confusa were immobilized for the production of dextran in alginate beads. The immobilized cells retained activity for three cycles of reactions without a decrease in dextran production. Free cells produced 1.3g/100ml and 3.35g/100ml of dextran after 48 hours in unoptimized medium (4% sucrose) and optimized medium (5% sucrose) respectively while immobilized cells produced 1.6g/100ml and 4.2g/100ml of dextran for three cycles in unoptimized and optimized medium respectively. There was 35-50% reduction in production in fourth cycle. Each cycle of fermentation was for 72 hours. Different parameters like size of inoculum, number of beads in a fixed volume of medium were also studied and optimized. The optimum inoculum size was 5%. Highest dextran yield was when 50 beads of 0.02 mm diameter were used for 50ml medium. Immobilized cells produced 1.6g/100ml and 4.2g/100ml of dextran in unoptimized and optimized medium respectively. The dextran produced by immobilized cells is of low molecular weight as indicated by HPLC analysis. The process of continuous production of low molecular weight food grade dextran is industrially very significant.